Operating at the very low end of the crassulacean acid metabolism spectrum: Sesuvium portulacastrum (Aizoaceae). (7th December 2018) - Winter, Klaus; Garcia, Milton; Virgo, Aurelio; Holtum, Joseph A M
Abstract : Leaves and stems of the pantropical coastal herb Sesuvium portulacastrum exhibit low-level CAM that is enhanced by drought-stress, emphasizing the need for careful characterization of photosynthetic physiology when selecting species to study the evolution of photosynthetic pathways. Abstract: Demonstration of crassulacean acid metabolism (CAM) in species with low usage of this system relative to C3 -photosynthetic CO2 assimilation can be challenging experimentally but provides crucial information on the early steps of CAM evolution. Here, weakly expressed CAM was detected in the well-known pantropical coastal, leaf-succulent herb Sesuvium portulacastrum, demonstrating that CAM is present in the Sesuvioideae, the only sub-family of the Aizoaceae in which it had not yet been shown conclusively. In outdoor plots in Panama, leaves and stems of S. portulacastrum consistently exhibited a small degree of nocturnal acidification which, in leaves, increased during the dry season. In potted plants, nocturnal acidification was mainly facultative, as levels of acidification increased in a reversible manner following the imposition of short-term water-stress. In drought-stressed plants, nocturnal net CO2 exchange approached the CO2 -compensation point, consistent with low rates of CO2 dark fixation sufficient to eliminate respiratory carbon loss. Detection of low-level CAM in S. portulacastrum adds to the growing number of species that cannot be considered C3 plants sensu stricto, although they obtain CO2 principally via the C3 pathway. Knowledge about the presence/absence of low-level CAM is critical when assessing trajectories of CAM evolution in lineages. The genus Sesuvium is of particular interest because it also contains C4 species.